How does(n't) Urban Shrinkage get onto the Agenda? Experiences from Leipzig, Liverpool, Genoa and Bytom. (16th December 2013) - Bernt, Matthias; Haase, Annegret; Großmann, Katrin; Cocks, Matthew; Couch, Chris; Cortese, Caterina; Krzysztofik, Robert
Abstract This article discusses the question of how urban shrinkage gets onto the agenda of public‐policy agencies. It is based on a comparison of the agenda‐setting histories of four European cities, Liverpool (UK), Leipzig (Germany), Genoa (Italy) and Bytom (Poland), which have all experienced severe population losses but show very different histories with respect to how local governments reacted to them. We use the political‐science concepts of 'systemic vs. institutional agendas' and 'policy windows' as a conceptual frame to compare these experiences. The article demonstrates that shrinkage is hardly ever responded to in a comprehensive manner but rather that policies are only implemented in a piecemeal way in selected fields. Moreover, it is argued that variations in institutional contexts and political dynamics lead to considerable differences with regard to the chances of making shrinkage a matter of public intervention. Against this background, the article takes issue with the idea that urban shrinkage only needs to be 'accepted' by policymakers who would need to overcome their growth‐oriented cultural perceptions, as has been suggested in a number of recent writings, and calls for a more differentiated, context‐sensitive view.